Performance and Robustness Testing of a Non-Invasive Mapping System for Ventricular Arrhythmias - Lesina, Krista; Szili-Torok, Tamas; Peters, Emile; de Wit, André; Wijchers, Sip A.; Bhagwandien, Rohit E.; Yap, Sing-Chien; Hirsch, Alexander; Hoogendijk, Mark G. (Frontiers in Physiology, 2022)
Background: The clinical value of non-invasive mapping system depends on its accuracy under common variations of the inputs. The View Into Ventricular Onset (VIVO) system matches simulated QRS complexes of a patient-specific anatomical model with a 12-lead ECG to estimate the origin of ventricular arrhythmias. We aim to test the performance of the VIVO system and its sensitivity to changes in the anatomical model, time marker placement to demarcate the QRS complex and body position. Methods: Non-invasive activation maps of idiopathic premature ventricular complexes (PVCs) using a patient-specific or generic anatomical model were matched with the location during electrophysiological studies. Activation maps were analyzed before and after systematically changing the time marker placement. Morphologically identical PVCs recorded in supine and sitting position were compared in a subgroup. Results: Non-invasive activation maps of 48 patients (age 51 ± 14 years, 28 female) were analyzed. The origin of the PVCs as determined by VIVO system matched with the clinical localization in 36/48 (75%) patients. Mismatches were more common for PVCs of left than right ventricular origin [11/27 (41%) vs. 1/21 (5%) of cases, p < 0.01]. The first 32 cases were analyzed for robustness testing of the VIVO system. Changing the patient-specific vs. the generic anatomical model reduced the accuracy from 23/32 (72%) to 15/32 (47%), p < 0.05. Time marker placement in the QRS complex (delayed onset or advanced end marker) or in the ST-segment (delaying the QRS complex end marker) resulted in progressive shifts in origins of PVCs. Altered body positions did not change the predicted origin of PVCs in most patients [clinically unchanged 11/15 (73%)]. Conclusion: VIVO activation mapping is sensitive to changes in the anatomical model and time marker placement but less to altered body position.